PERGULATAN ANTARA PEMIKIRAN LIBERAL DAN ANTI â LIBERAL Studi Pertarungan Wacana dalam Tubuh NU Sejarah, Substansi dan Jawaban - , REZA ZULFIKAR W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Liberalism is an influential thought for the development of religious thought in the Islamic world. In Indonesia, there is almost no Muslim communities that is completely free from the influence of the liberal thinking. NU (Nahdlatul Ulama) as the largest Muslim organization in Indonesia is one such example. NU (Nahdlatul Ulama) has the large mass and long experience that triggers the entry of liberal ideas and born a new phenomenon for the development of knowledge in Islam. The impact of this phenomenon will obviously make the development of thinking in the NU becoming increasingly dynamic. It was due to the influx of liberal ideas that is not only give ânew colorâ for NU, but it also has led to resistance in it. Resistance is then appeared in a form of struggle thought in the arena of perspektive discourse. This study focused on the struggle thought in the arena of perspektive discourse within NU. NU as the largest Muslim organization in Indonesia will be used as research object. While the struggle thought that occurs as a result of the entry and development of the liberal ideas become a major issue to be raised. This issue will be compiled using the glasses of perspektive discourse that presents how the actors - actors involved is struggling to get his dominance and hegemony discourse within NU. The research method used was a qualitative method. It is a case study by asking a fundamental question of \"how the struggle between Liberal and anti-Liberal thinking as a form of perspektive discourse that occurs in the body of NU? In this study, it was found that the rise of perspektive discourse is because of the inclusion of liberal thought in the NU and it get a different response. This gave rise to the rejection response in the form of discourse sparring anti - liberal. The hostility is increasingly emphasized both the substance of the debate in various, ranging from differences in responding to the issue - a crucial issue in the midst of the people to the differences in the level of scientific tradition. Actually their main pupose is dominance of the discourse. But what happens is the feud that actually leads to a consolidation of ideas.